Persinggungan Politik Islam dan Islam Politik: Genealogi dan Perkembangan Islam di Era Orde Baru - Alfanny, M. Sa’ad; Dh, Achmad Zuhdi; Musdalifa; Muhammad, Ferhadz A. (Brawijaya University, 2025)
The New Order era became a crucial point in the relationship between politics and religion in Indonesia, characterised by authoritarian policies and ideological propaganda that generated social tensions. The main debate revolved around the position of religion within the state, which fuelled conflicts in religious practice. The New Order regime applied repressive and co-optative strategies towards Islam, shaping a religious mould that tended to be subservient to power. This research aims to trace the development of Islam during this period by distinguishing between political Islam and political Islam. Through a qualitative approach and descriptive analysis, this study focuses on the relationship between state policy and muslim religious expression, as well as its impact on Islamic socio-political dynamics, in order to re-understand the configuration of the relationship between Islam and the state in the New Order era.